2013
DOI: 10.1073/pnas.1301171110
|View full text |Cite
|
Sign up to set email alerts
|

Ultradian metabolic rhythm in the diazotrophic cyanobacterium Cyanothece sp. ATCC 51142

Abstract: The unicellular cyanobacterium Cyanothece sp. American Type Culture Collection (ATCC) 51142 is capable of performing oxygenic photosynthesis during the day and microoxic nitrogen fixation at night. These mutually exclusive processes are possible only by temporal separation by circadian clock or another cellular program. We report identification of a temperature-dependent ultradian metabolic rhythm that controls the alternating oxygenic and microoxic processes of Cyanothece sp. ATCC 51142 under continuous high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 31 publications
(42 reference statements)
2
34
0
Order By: Relevance
“…We envision a stoichiometric whole-cell model, with a focus on energetic constraints, that allows us to assess the optimality of metabolic strategies in diverse environments. Of particular interest are the energetic implications of carbon cycling (43), light damage and its repair, and the coupling of metabolic processes to the cell cycle, as well as the temporal segregation of incompatible metabolic processes, such as nitrogen fixation in certain cyanobacteria (44). We conjecture that global resource allocation models, together with the methodology described here, will allow us to assess the condition-dependent cost and benefit of individual genes (45) in the context of a growing cell, and thereby facilitate the study of metabolic adaptations and metabolic diversity of cyanobacteria (46) with the ultimate aim of understanding the limits of phototrophic growth in complex environments.…”
Section: Discussionmentioning
confidence: 99%
“…We envision a stoichiometric whole-cell model, with a focus on energetic constraints, that allows us to assess the optimality of metabolic strategies in diverse environments. Of particular interest are the energetic implications of carbon cycling (43), light damage and its repair, and the coupling of metabolic processes to the cell cycle, as well as the temporal segregation of incompatible metabolic processes, such as nitrogen fixation in certain cyanobacteria (44). We conjecture that global resource allocation models, together with the methodology described here, will allow us to assess the condition-dependent cost and benefit of individual genes (45) in the context of a growing cell, and thereby facilitate the study of metabolic adaptations and metabolic diversity of cyanobacteria (46) with the ultimate aim of understanding the limits of phototrophic growth in complex environments.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that 12-h genes have alternating peak heights, which is consistent with our observation at the protein level of pilin polypeptide PilA-like (signal transduction), carbonate dehydratase (nitrogen metabolism), 2-hydroxy-6-oxohepta-24-dienoate hydrolase (no specific function), and a putative uncharacterized protein. Recent reports describe rhythms shorter than 24 h, called ultradian rhythms, which have also been reported to occur in related cyanobacteria such as Cyanothece (48,49) and Prochlorococcus (50).…”
Section: Focusing On Proteins Displayingmentioning
confidence: 96%
“…As a result, cyanobacteria are nutritionally independent to a large degree (Meeks, 1988) and occupy diverse habitats, ranging from freshwater and oceanic ecosystems, temperate soils to extreme environments such as hot springs and deserts (Herrero et al, 2001). To counter the adverse effects of oxygen evolution from photosynthesis on BNF, diazotrophic cyanobacteria have developed strategies such as temporal separation of oxygenic photosynthesis and micro-oxic NF (Cerveny et al, 2013) and formation of thick-walled, non-photosynthetic heterocysts with microaerobic interiors that are conducive for NF (Wolk et al, 1994).…”
Section: Cyanobacterial Associationsmentioning
confidence: 99%